Outcomes of stent retriever thrombectomy in basilar artery occlusion: an observational study and systematic review. Issue 5 (18th May 2015) - Gory, Benjamin; Eldesouky, Islam; Sivan-Hoffmann, Rotem; Rabilloud, Murielle; Ong, Elodie; Riva, Roberto; Gherasim, Dorin Nicolae; Turjman, Alexis; Nighoghossian, Norbert; Turjman, Francis
Abstract : Background: Basilar artery occlusion (BAO) remains one of the most devastating subtypes of stroke with high mortality and poor outcome. Early recanalisation is the most powerful predictor of favourable outcome in patients with stroke, and may be improved with mechanical thrombectomy using stent retriever devices. However, the benefit in functional outcome and safety of stent retrievers are not yet well known. The aim of this study was to assess efficacy and safety profiles of stent retriever thrombectomy in BAO patients with stroke. Methods: We analysed data retrospectively from our consecutive clinical series and conducted a systematic review and meta-analysis of all previous studies of stent retriever thrombectomy in BAO patients with stroke between November 2010 and April 2014. Results: From March 2010 to March 2013, 22 patients with acute BAO were treated with a Solitaire stent retriever in our series. Favourable outcome was significantly associated with younger age and distal BAO. The literature search identified 15 previous studies involving a total of 312 subjects. In the meta-analysis, including our series data, the recanalisation rate (Thrombolysis In Cerebral Infarction (TICI) score ≥2b) reached 81% (95% CI 73% to 87%). The rate of symptomatic intracranial haemorrhage was 4% (95% CI 2% to 8%), favourable outcome (modified Rankin Scale (mRS) ≤2 at 3 months) was found in 42% (95% CI 36% to 48%) and mortality rate was 30% (95% CI 25% to 36%). Conclusions: Stent retriever thrombectomy is a safe treatment modality for patients with stroke presenting with BAO. Although the stent retrievers showed a good recanalisation rate, there are currently no randomised clinical trials to assess its clinical efficacy in comparison with the reference treatment.